PODCAST UTILIZATION TO ENHANCE STUDENT'S LISTENING SKILL - Deri Eka Putra; Rahma Dianti, M.Pd (Universitas Tridinanti Palembang, 2022)
Listening skill is one of language skills which is crucial to promote language users’ communicative competences. It is essential for the teachers to utilize appropriate media to create a supportive learning atmosphere.Podcast as one of ICT tools can be optimized to provide the students with periodical listening sources to help practicing the student’s listening skill. This research explored Podcast utilization in listening class and aimed at finding out whether or not Podcast utilization could enhance students’ listening comprehension and compare the students’ listening comprehension between the students who were taught using Podcast and the students who were not taught using Podcast. A quasi experimental research was applied as the research design. This research involved eighty-eight students selected using purposive sampling technique. Listening comprehension test was administered to obtain the data. The obtained data were analyzed by using Paired Sample T-test and Independent Sample T-test. The result of Paired Sample T-test showed that there was a significant progress in student listening comprehension after they got treatment by using Podcast. The result of Independent Sample T-test revealed that the progress of experimental group exceeded the progress of control group in their listening comprehension. It proved that utilizing Podcast could enhance students’ listening skills.Keywords:Podcast, listening skills, ICT utilization